2018
DOI: 10.1021/acsnano.7b07060
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Profiling of Single Extracellular Vesicles

Abstract: Extracellular vesicles (EV) are a family of cell-originating, membrane-enveloped nanoparticles with diverse biological function, diagnostic potential, and therapeutic applications. While EV can be abundant in circulation, their small size (~4 order of magnitude smaller than cells) has necessitated bulk analyses, making many more nuanced biological explorations, cell of origin questions, or heterogeneity investigations impossible. Here we describe a single EV analysis (SEA) technique which is simple, sensitive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
347
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 300 publications
(353 citation statements)
references
References 56 publications
6
347
0
Order By: Relevance
“…82 In this approach, EVs are immobilized inside a microfluidic chamber, immuno-stained, and imaged. With the vesicles immobilized on the chip surface, the achievable signal-to-noise ratio from each vesicle is generally much higher than that when the vesicles are free-floating in solution or under flow condition.…”
Section: Physical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…82 In this approach, EVs are immobilized inside a microfluidic chamber, immuno-stained, and imaged. With the vesicles immobilized on the chip surface, the achievable signal-to-noise ratio from each vesicle is generally much higher than that when the vesicles are free-floating in solution or under flow condition.…”
Section: Physical Characterizationmentioning
confidence: 99%
“…EVs from Gli36-WT and Gli36-IDH1R132 cells lines clustered similarly, whereas EVs from Gli36-EGFRvIII cells showed distinct clusters. Reprinted with permission from Ref 82. Copyright 2017 American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…[5] However, subtle molecular differences at the single EV level may yield significant variation in EV biological functions, [6] and the highly heterogeneous nature of EV population demands the development of techniques capable of profiling individual EVs. [4] Most recently, single EV counting with a nanochip [7] and imaging single vesicles with advanced fluorescence microscopy [8] have been reported, and showed that EVs from different cell of origin can carry distinct surface markers mimicking their parent cells. Still, they require EV immobilization steps, limiting the down-stream investigations on EV functions and biogenesis.…”
mentioning
confidence: 99%
“…If the signals from both markers can be acquired simultaneously, the flow plots should directly show the presence of EV sub-populations in a heterogeneous EV mixture without the help of statistical tools, which is necessary for single vesicle analysis using microscopic methods. [8] Herein, we designed a “dual hybridization cascade system” to simultaneously amplify signals from HER2 and CD63 on a single EV by two separate hybridization cascade reactions (Table S1). In this system, CD63 signal was still derived from the streptavidin-conjugated QDs, but HER2 signal was from the Alexa660 labelled DNA tag hybridized with the overhang in H3 on the HCR product (Fig.…”
mentioning
confidence: 99%
“…As an example, antibodies against the tetraspanin CD63 have been widely applied to exosome isolation from the plasma of patients with ovarian cancer, breast cancer, and glioblastoma . However, anti‐CD63 is not a specific biomarker for any one cancer, and its expression is known to vary depending on the type of cancer . Recent studies using clinical samples showed that only 69.56% of lung cancer patients have CD63 positive exosomes with comparably low absolute expression level compared to other exosomal markers .…”
Section: Introductionmentioning
confidence: 99%